(untitled) (Journal of Fatima Jinnah Medical University, 2019)
Background: Models have been developed to predict a variety of outcomes, for all cardiac surgery and also for specific cardiac surgery procedures. The most broadly utilized model for anticipating mortality in cardiovascular surgery was EuroSCORE I which has been upgraded in recent times to EuroSCORE II. The objective of the present study was to evaluate the efficacy of the EuroSCORE II in anticipating the mortality in patients experiencing cardiac surgery. Subjects and methods: Cross-sectional observational study from a sample of 101 cardiac surgery patients was conducted to evaluate the outcomes (length of stay at ICU and hospital and mortality) of postoperative cardiac surgery in relation to EuroSCORE II at Punjab Institute of Cardiology Lahore from 22nd April, 2016 to 15th December, 2016. Results: Mean values of WBCs, serum creatinine and bilirubin total were significantly increased from preoperative to postoperative-I and a minor decrease on the postoperative II readings whereas mean values of hemoglobin and platelets constantly (p-value<0.01) declined after surgery. Mean values of blood urea and ALT increased sequentially during preoperative, postoperative-I and postoperative-II laboratory investigations. In addition, positive relationship of EuroSCORE II with ICU stay (r = 0.205, p-value<0.05) and ventilation time (r = 0.232, p-value<0.05) were observed. In addition to these results, there were 98 (97.0%) patients discharged after cardiac surgery and 3 (3.0%) patients expired. Conclusion: The risk prediction from EuroSCORE II is best suited for low and medium risk group patients but it was not appropriate for high risk patients.